2020
DOI: 10.1136/bmjebm-2019-111309
|View full text |Cite
|
Sign up to set email alerts
|

Intervention reporting of clinical trials published in high-impact cardiology journals: effect of the TIDieR checklist and guide

Abstract: BackgroundRandomised controlled trials (RCTs) provide the highest-level of evidence among primary research in cardiovascular medicine. Yet, even the best trial may be less useful if it fails to provide an accurate means of reproducibility. Unfortunately, discrepancies in the standards of trial reporting have been persistent in previous trials. The Template for Intervention Description and Replication (TIDieR) checklist aims to improve research efficacy by setting standards for quality intervention reporting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Also, within the articles, there was little to no mention of the TIDieR checklist and reporting of interventions in accordance with it, in line with other systematic reviews. Investigating implementation in the cardiovascular medicine literature, Palmer et al 41 found over one-fifth failed to report the dose of the treatment received (item 11). Within behaviour change research similar results to this review have been found, 42 with the maximum dose available always reported, but other elements of dose poorly described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, within the articles, there was little to no mention of the TIDieR checklist and reporting of interventions in accordance with it, in line with other systematic reviews. Investigating implementation in the cardiovascular medicine literature, Palmer et al 41 found over one-fifth failed to report the dose of the treatment received (item 11). Within behaviour change research similar results to this review have been found, 42 with the maximum dose available always reported, but other elements of dose poorly described.…”
Section: Discussionmentioning
confidence: 99%
“… 41 Therefore, broader dissemination of the TIDieR checklist or incorporating the checklist within item 5 of the CONSORT statement, could improve reporting, as the information would be required by journals for publication. 41 Poor implementation of the TIDieR checklist could also be due to the guidelines being too broad and generic and difficult for authors to adapt to their own interventions. 43 Making the TIDieR checklist clearer and developing customised versions for specific intervention types could increase implementation of the checklist guidelines and ultimately improve intervention description and reporting.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted in tandem with other studies that evaluated the completeness of intervention reporting across clinical specialties. Since these studies used a common methodology, these methods have also been described elsewhere (12)(13)(14)(15).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, an extension of this guideline focusing only on the interventions section is available - the TIDieR reporting guideline [14]. Among the exercise-based intervention (EBI) CVR studies, about half provide an adequate reporting of interventions [3], without relevant improvement over time regardless of the scientific community effort and editorial policies to improve the quality of reporting of manuscripts [15].…”
Section: Introductionmentioning
confidence: 99%